GAMBARAN PENGGUNAAN OBAT ANTIDIABETIK PADA PASIEN DIABETES MELITUS DI RSUD TUAN RONDAHAIM KABUPATEN SIMALUNGUN PERIODE APRIL – JUNI 2024 - Lusiana Siburian; Arsiaty Sumule; Dilla Sastri (CV. ADIBA ADISHA AMIRA, 2024)
Diabetes Mellitus (DM) is a chronic metabolic disorder disease characterized by increased levels of glucose in the blood accompanied by impaired metabolism of carbohydrates, fats and proteins. To insulin. Adherence to treatment in DM patients is very important for the success of this therapy, this is done to prevent complications. The purpose of this study is to find out the description of type 2 DM patients, including gender, age on medication adherence.This study used a descriptive method. The population in this study was all prescriptions for type 2 Diabetes Mellitus patients in the period April – Juny 2024. The secondary samples in this study were all prescriptions for Diabetes Mellitus patients containing oral anti diabetic drugs using purposive sampling technique. Researched all prescriptions containing oral anti diabetic drugs, including drug classes and types of drugs.The results showed that the use of antidiabetic drugs in type 2 DM patients at the RSUD Tuan Rondahaim was Glimepiride 40,7%, Insulin Flexpen 26,4%, Metformin 22,9% and Acarbose 10,1 %.